Functional separator with lower resistance toward lithium ion transport for enhancing the electrochemical performance of lithium ion batteries - Kim, Ki Jae; Kwon, Yong Kab; Yim, Taeeun; Choi, Wonchang (한국공업화학회, 2019)
By chemical treatment with benzoyl peroxide, oxygen-containing functional groups can be successfully introduced to the surface and interior of the PE separator, resulting in improved wettability and high electrolyte uptake without sacrificing mechanical and physicochemical properties. Hence, lithium ion transport across the PE separator treated by benzoyl peroxide is effectively facilitated by the formation of oxygen functional groups, leading to improved ionic conductivity. The LiB cells assembled with the PE separator treated by BPO exhibit remarkable rate capability and outstanding capacity retention (98.1%) after 70 cycles. (C) 2018 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.